THE IMPORTANCE OF INTERNATIONAL ASSESSMENT PROGRAM - PISA AND PIRLS IN TEACHING MODERN PHYSICS - Mirzayeva Umidaxon Murodjon qizi (Web of Journals Publishing, 2025)
This article provides information about modern educational programs PISA and PIRLS, and outlines the directions of international educational programs.
Keywords: Testing, platform, international educational programs, concept, creative thought.